Relevansi Mindfulness dalam Al-Qur’an terhadap Fenomena Quarter Life Crisis - Sukmana; Muhammad Azizan Fitriana; Ahmad Syukron (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
This study examines the relevance of the concept of mindfulness in the Qur’an to the phenomenon of quarter-life crisis experienced by young Muslims aged 18-29 years. Quarter-life crisis is characterized by anxiety, confusion, and restlessness related to life goals, identity, and personal achievement. Using the thematic interpretation analysis method, this study examines five pairs of Qur’anic mindfulness concepts related to the symptoms of quarter-life crisis: al-murāqabah with al-khauf, at-taqwā with aḍ-ḍaiq, aż-żikr with al-ḥuzn, al-khusyū’ with al-halū’, and at-tawakkal with aḍ-ḍaiq. The findings show that the five pairs of concepts are integrated in a holistic approach based on al-iḥsān that harmonizes the dimensions of insāniyyah (humanity), rūḥāniyyah (spirituality), and rabbāniyyah (divinity). The novelty of this research lies in the development of a Qur’anic mindfulness framework that not only offers practical strategies for managing psychological symptoms of quarter-life crisis, but also provides a transformative spiritual dimension. Based on the research results, the Qur’anic mindfulness approach centered on al-iḥsān has the potential to shift the crisis phase of the young generation into a valuable spiritual development momentum, and contributes to integrating Islamic spiritual values ​​with the latest developmental psychology studies.